Potentialities of Bagbag area, northwestern Mediterranean coast of Egypt, as a natural range - Ahmed, M. A.; EL-Khouly, A. A.; Khalifa, E. A. (2007)
The vegetation in Bagbag area is formed of eight plant community types dominated and co-dominated by: Asphodelus ramosus, Thymelaea hirsuta, Deverra tortuosa, Stipa capensis, Lygeum spartum, Plantago albicans, Haloxylon scoparium and H scoparium - T. hirsuta. Seventeen associated palatable species were recorded in these communities as weU as eleven perennials and six annuals. Asphodelus ramousus community comprises the highest number of palatable species. Six palatable perennial species distributed in Bagbag area were selected to evaluate their potentiality for the development of this area. These species are: Gymnocarpos decander, Helianthemum lippii, Echiochilon fruiticosumm, Deverra tortousa, Periploca angustifolia and Lycium shawii. Deverra tortuosa has proven to have the density and importance value (IV) (7.0 and 32.3, respectively) compared with the other palatable studied species, while P. angustifolia had the lowest of density and importance value (0.2 and 2.9). The highest percentage of crude protein (CP), TON and DCP were determined in the grazeable parts of P. angustifolia followed by L. shawii. Most of the palatable species had low values of lV and density being dwarf due to heavy grazing. Though the pasture condition of the study area is generally high, the vegetation potential is promising. Whereas multiple improvement and development opportunities in this study area are really available.
Includes references.
Summary in Arabic.
1
Keywords: Range plants -- Egypt; Rangelands -- Egypt